Degradasi Methyl Orange Secara Fotosonolisis Menggunakan Katalis ZnO/TiO2 - Nurhafizah Nurhafizah; Hary Sanjaya; Hardeli Hardeli; Yohandri Yohandri (Departemen Kimia FMIPA UNP, 2021)
Abstract— The textile industry in Indonesia is increasing as a result of which more waste is produced, one of which is dye waste. The resulting waste has an impact on the surrounding environment. To reduce the impact caused by the waste, there are several methods used, one of which is degradation using photosonolysis method. In this study, the degraded dye was methyl orange using a ZnO/TiO2 catalyst with the photosonolysis method. This study aims to determine the optimum time and optimum doping of TiO2 in degrading methyl orange. The percentage of degradation was obtained from the absorbance value measured using a UV-VIS spectrophotometer. The maximum wavelength measurement result of methyl orange obtained is 463 nm. The result showed that the optimum radiation time to degrade methyl orange was 75 minutes with a degradation percentage of 60,568%. On the effect of the concentration of the ZnO/TiO2 catalyst, the optimum degradation percent was 27,317% at a concentration of 10%. For catalyst analysis using UV-DRS, the band gap value of ZnO/TiO2 was 10 % was 3,17 eV.